MILITARY REALIA IN FRENCH AND UZBEK LANGUAGES: A COMPARATIVE AND TRANSLATIONAL ANALYSIS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines military realia in French and Uzbek from comparative and translation perspectives. Military realia represent culture-specific lexical units that reflect the historical, social, and military traditions of a nation. The study analyzes military ranks, names of weapons, military structures, and culture-bound concepts in both languages. Particular attention is paid to translation problems and methods such as transliteration, calque, descriptive translation, and functional equivalence. The research demonstrates that many French military realia lack direct equivalents in Uzbek due to differences in military organization and historical development. The findings emphasize the importance of linguistic and cultural factors in translating military terminology.
Keywords: Military realia, French language, Uzbek language, comparative analysis, translation studies, military terminology, cultural specificity, transliteration, functional equivalence.